Security and Privacy Concerns for the Modern Technology of Internet of Things - Majid Baba, Samiya; Bala, Indu (Asian Journal of Engineering and Applied Technology, 2022)
The Internet of Things (IoT) is present in every aspect of our lives. They are used in our households, in hospitals, and outside to monitor and report environmental improvements, deter fires, and perform a variety of other useful functions. However, both of these advantages can come at the expense of significant security and risks privacy. Several academic research have been conducted to counteract these issues and figure out a better way to remove or minimise the threats to the user’s privacy and protection specifications in IoT devices. The survey is divided into four parts. The first section would look at the most important shortcomings of IoT devices and how to overcome them. The description of IoT attacks will be presented in the second section. The final section would look at security problems at various layers.